Organizational Support and Work Engagement: Onsite, Hybrid, and Remote Work during COVID-19 - Kirsikka Selander; Tuomo Alasoini (Nordic Journal of Working Life Studies)
We analyzed the association of job autonomy, mental demands, and organizational support on work engagement and the moderating role of organizational support between mental demands and work engagement. We also examined differences in these factors among onsite, hybrid, and remote workers during the COVID-19 pandemic using data from the Finnish MEADOW survey. Results showed that the remote workers had highest job autonomy, but no other significant differences were found. Job autonomy was positively associated with work engagement, while mental demands had a negative association with it. Organizational support had the strongest positive association with work engagement, and it was able to moderate the negative association between mental demands and work engagement. We conclude that the remote work cannot be classified as good or bad; rather, the question is more on how work is organized and managed. The new environment where remote work is increasingly done, however, presents several challenges for managers and supervisors.